A three dimensional sulfur/reduced graphene oxide with embedded carbon nanotubes composite as a binder-free, free-standing cathode for lithium–sulfur batteries. Issue 69 (11th September 2017) - Ying, Kongqing; Tian, Ran; Zhou, Jie; Li, Hua; Dugnani, Roberto; Lu, Yanyan; Duan, Huanan; Guo, Yiping; Liu, Hezhou
Abstract : The free-standing electrodes are synthesized by an eco-friendly method with sulfur/carbon nanotubes embedded in the basal plane of graphene oxide. Abstract : Binder-free and free-standing electrodes have been regarded as an attractive and promising structure in lithium–sulfur batteries. In this work we describe how a free-standing sulfur/reduced graphene oxide with embedded carbon nanotubes electrode has been synthesized by a novel, facile and eco-friendly method taking advantage of the solubility difference of polar and nonpolar materials. First, the nonpolar elemental sulfur is dissolved in a weak polar solvent (ethanol) by intensive ultrasonication. During a subsequent heavy polar solvent (deionized water) drop-wise procedure, nano-sized sulfur particles are precipitated from the ethanol and deposited on the dispersed carbon nanotubes and graphene oxide. Noticeably, since ascorbic acid is taken as the reducing agent for graphene oxide at 75 °C, the process produces no toxic byproducts. Besides, the 'as-designed' sulfur/reduced graphene oxide with embedded carbon nanotubes graphene oxide displays a unique structure with both the sulfur and carbon nanotubes embedded in the basal plane of reduced graphene oxide. The manufactured electrode is found to exhibit excellent rate capability and cyclability, with the maximum capacity of 1025 mA h g −1 observed in the third cycle and a stable capacity of 704 mA h g −1 after 100 cycles.